2012
DOI: 10.1021/ma300621g
|View full text |Cite
|
Sign up to set email alerts
|

Solution Behavior of Double-Hydrophilic Block Copolymers in Dilute Aqueous Solution

Abstract: The self-assembly of double-hydrophilic poly(ethylene oxide)–poly(2-methyl-2-oxazoline) diblock copolymers in water has been studied. Isothermal titration calorimetry, small-angle X-ray scattering, and analytical ultracentrifugation suggest that only single polymer chains are present in solution. In contrast, light scattering and transmission electron microscopy detect aggregates with radii of ca. 100 nm. Pulsed field gradient NMR spectroscopy confirms the presence of aggregates, although only 2% of the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 42 publications
(65 reference statements)
4
89
0
4
Order By: Relevance
“…At this point, we assume that this turbidity originates from the aggregation of the star-shaped block copolymers, although both blocks are of hydrophilic nature. Such behavior has also been described for water-soluble homo-and block copolymers in the literature [12,19,[56][57][58]. In some cases, the unexpected aggregation of double-hydrophilic block copolymers was explained by slight differences in the hydrophilicity of both blocks [50,58].…”
Section: Study Of Star-shaped [Peo 28 -B-petox X ] 8 In Non-selectivesupporting
confidence: 67%
“…At this point, we assume that this turbidity originates from the aggregation of the star-shaped block copolymers, although both blocks are of hydrophilic nature. Such behavior has also been described for water-soluble homo-and block copolymers in the literature [12,19,[56][57][58]. In some cases, the unexpected aggregation of double-hydrophilic block copolymers was explained by slight differences in the hydrophilicity of both blocks [50,58].…”
Section: Study Of Star-shaped [Peo 28 -B-petox X ] 8 In Non-selectivesupporting
confidence: 67%
“…On the contrary, at 70 °C, the pEtOx blocks did not coalesce into a liquid bulk phase, since both blocks were sufficiently hydrophobic. Schlaad, Taubert et al studied the solution behavior of double-hydrophilic poly(ethylene oxide)-block-pMeOx [169]. Pulsed field gradient NMR spectroscopy confirmed the presence of aggregates, despite the block copolymer's double-hydrophilic character.…”
Section: Self-assembly Of Diblock Copoly(2-oxazoline)smentioning
confidence: 99%
“…[15][16][17][18] One of the first reports of such behavior was by Taubert et al,who demonstrated that double hydrophilic block copolymers can form lyotropic mesophases in pure water, which they could easily visualize by polarization microscopy.They suggested that the mesophases were just layers of water stacked on top of each other, separated only by the diblocks.…”
mentioning
confidence: 99%
“…[16] They determined that only asmall fraction of polymer in solution was able to form their hydrated aggregates,w hich had characteristic features indicating vesicle formation, but overall it was difficult to confirm the exact nature of the aggregates owing to their low overall number and size.…”
mentioning
confidence: 99%